A New Species of Begonia (Begoniaceae) from the Eastern Cordillera of Colombia - Jara-Muñoz, O.a.; Moonlight, P.w.; Zabala-Rivera, J.c. (Phytotaxa, 2023)
A new species of Begonia section Ruizopavonia is here described and illustrated, and a key for the Colombian species of the section is also provided. The new species grows on the eastern side of the eastern Colombian Cordillera and can be recognized among species in the same section bearing staminate flowers with 4 tepals and pistillate flowers with 3 tepals by the larger outer tepals on both the staminate and pistillate flowers (>9.5 mm long). We assess the new species as Endangered (EN) under IUCN criteria; its protection is therefore recommended.